Safety of triazole antifungals: a pharmacovigilance study from 2004 to 2021 based on FAERS. (December 2022) - Chai, Shuang; Zhan, Jing-Lun; Zhao, Li-Mei; Liu, Xiao-Dong
Background: Triazole antifungals are widely used as broad-spectrum antifungal activity; however, there are many undetected and unreported adverse events (AEs). Methods: Data from the Food and Drug Administration Adverse Event Reporting System (FAERS) from the first quarter (Q1) of 2004 to the third quarter (Q3) of 2021 were selected for disproportionality analysis to assess the connection between antifungal triazoles, and AEs and important medical events (IMEs). Results: A total of 22, 566 records associated with triazole antifungals were identified, with 9584 triazole antifungal–IME pairs. The following system organ classes (SOCs) appeared as significant signals: 'Endocrine disorders' [reported odds ratio (ROR) = 167.94], 'Metabolism and nutrition disorders' (ROR = 46.30), and 'Skin and subcutaneous tissue disorders' (ROR = 21.37). Strong signals were observed with respiratory failure, rash, hepatic function abnormal, and hypokalemia. Uncommon security signals included a change in the QT interval, neurotoxicity, pseudoaldosteronism, and hallucinations. Conclusion: Various triazole antifungals cause AEs of different types and intensities of association. Our results are broadly consistent with prescribing information and previous studies; however, additional pharmacoepidemiological studies are required to verify AEs with modest incidence but high signal. Plain Language Summary: A study on the adverse effects of triazole antifungals Introduction: The triazole antifungals we studied include fluconazole, itraconazole, voriconazole, posaconazole, and isavuconazole. Triazole antifungals are widely used as broad-spectrum antifungals; however, there are many undetected and unreported adverse events (AEs). Materials and Methods: The Food and Drug Administration Adverse Event Reporting System (FAERS) database contains AEs reported to the FDA by different countries regarding post-marketing drugs. Through the FAERS database, we retrieved a total of 22, 566 AE reports related to triazole antifungals. We not only counted information about patients' gender, age, weight, reporting country, outcome indicators, and indications but also analyzed the system organ classes (SOCs) of AEs, and the number of reported drug-related AEs and the degree of relevance. Results: We found a total of 22, 566 records related to triazole antifungal agents, of which 9584 reports made important medical events (IMEs) about triazole antifungal agents, which are serious AEs. The following SOCs appear as important signals: 'endocrine disorders', 'metabolic and nutritional disorders', and 'skin and subcutaneous tissue disorders'. Triazole antifungals produce AEs, such as respiratory failure, rash, hepatic function abnormal, and hypokalemia. They also produce uncommon AEs, including changes in the QT interval, neurotoxicity, pseudoaldosteronism, and hallucinations. Conclusion: By analyzing data from the FAERS database, we identified more AEs associated with these five triazole antifungals than were indicated in the instructions and our findings provide additional insight into triazole-related AEs to inform clinicians before and during treatment.